Enhancing science teachers’ competencies in Tanzania: The utilization of teaching and learning resources - Kanyabwoya, Angelina; Bwagilo, Huruma Olofea; Mugaya, Samweli, Tumain (Journal of Multidisciplinary Research and Development, 2026)
This study examines how teaching and learning resources can enhance competencies of science teachers at diploma-level teacher training colleges. A multiple case study research design was employed. Qualitative methods, such as interviews, focus group discussions, documentary reviews and observations, were used to collect data from 66 respondents, which was analyzed using thematic analysis. The findings revealed that few science tutors utilized teaching and learning resources effectively. This was due to inadequate of skills, limited administrative supports, delays in providing teaching and learning materials, large classes and heavy teaching workloads. Despite the minimal availability of teaching and learning resources and the willingness of science tutors to utilize these resources in science teaching and learning, the study concludes that their implementation in the classroom remains ineffective. Consequently, student teachers are likely to remain incompetent in science subjects. The study recommends the effective use of teaching and learning resources, their timely purchase, and indoor training provision.